An Analysis of Phrases in Technology Brands Slogan and its Contribution in Teaching English Grammar - Rizal, Ifan Nur; Sumardiyani, Listyaning; Lestari, Maria Yosephine Widarti (Universitas PGRI Semarang, 2022)
A phrase is a group of words that serves as a unit of a sentence. There are several types of phrases namely noun phrase, verb phrase, adjective phrase, adverb phrase, and prepositional phrase. A phrase used in an advertisements and promotional activities such slogans. Every commercial product makes a slogan to attract the attention of target market. This study is a content analysis which aimed at analyzing kind of phrases in syntax categories that found in English technology brand slogans and its contribution in teaching English grammar. The method used in this study was qualitative descriptive to investigate and describe kind of phrase in 40 technology brand slogans and clarify the contribution of the analysis to teaching English grammar. In collecting the data, researcher used note taking. The result shown that researcher find some phrases form. The analysis was recommended by the researcher as a teaching media since its accordance with the English teaching syllable.